(untitled) (Studia Prawnicze / The Legal Studies, 2008)
Nowelizacją z dnia 2 lipca 2004 r. wprowadzono do ustawy Prawo lotnicze (dalej p.lot.) art. 122a, stanowiący podstawę do zestrzelenia porwanego przez terrorystów samolotu cywilnego, również z pasażerami na pokładzie, jeżeli „wymagają tego względy bezpieczeństwa państwa” i jest on „użyty do działań sprzecznych z prawem, a w szczególności jako środek ataku terrorystycznego z powietrza”. Chodzi oczywiście o potencjalne posłużenie się nim jak bronią, w celu rozbicia o wieżowiec czy w centrum miasta, tak jak miało to miejsce 11 września 2001 r. w Stanach Zjednoczonych. W zakresie procedury i przesłanek wspomniany przepis odsyła do odpowiedniej części ustawy o ochronie granicy państwowej4(art. 18b). Nie rozwodząc się w tym miejscu nad rozwiązaniem polskim, należy wspomnieć, iż podobne regulacje zostały również przyjęte w Niemczech, Rosji i na Węgrzech. Jednak odpowiednie przepisy niemieckiego Luftsicherheitsgesetz (dalej LuftSiG) zostały uchylone wyrokiem Bundesverfassungsgerichtu (niemieckiego federalnego Trybunału Konstytucyjnego, dalej BVerfG) z dnia 15 lutego 2006 r., m.in. ze względu na sprzeczność takiego rozwiązania z podstawowymi prawami człowieka. Przyjęcie polskich przepisów przeszło niemal całkowicie niezauważone zarówno przez opinię publiczną, jak i prawników. Wydają się one przy tym niezwykle podobne do uchylonych przez Bundesverfassungsgericht, argumenty zaś przytoczone przez Trybunał zdają się mieć walor uniwersalny. Celowe wydaje się zatem prześledzenie losów niemieckiej ustawy oraz następnie odpowiedź na pytanie, czy również odpowiednie regulacje polskich ustaw pozostają w sprzeczności z konstytucyjnie chronionymi wartościami. After the attacks of 9.11 many countries, including Poland and Germany, in troduced regulations allowing to shoot down a civilian airplane used by terrorists to conduct an air attack. In Germany adopting the appropriate regulation was preceded by a lively discussion in the national Parliament as well as in the na tionwide press. Even though the bill was executed, it was the subject to a consti tutional complaint and to the decision of the Bundesverfassungsgericht, which on 15th February 2006 ruled that the law was an infringement on the basic human rights. According to the Tribunal, allowing to shot down a hijacked, civilian plane with passengers on board constitutes the breach of their right to life and uman dignity. A state may not deprive those individuals of its protection, especially it is not allowed to compare the value of the life of individuals endangered by the potential terrorist attack and those on board of the plane. Such a comparison may not be made neither based on the time, that the passengers have left to live, nor on the number of individuals, that would have to be killed and the number of ones rescued on the ground. The right of citizens to have their life protected by the state authorities serves them until the very end and the state may not deprive them of such a protection. The passengers may neither be treated as a part of a "weapon" used against the terrorists. In Poland the execution of a similar bill went by unnoticed by the public opin ion and the press. Moreover in the phase of parliamentary work no constitutional uncertainty was expressed. It was only not so long ago that the First Chairman of the Supreme Court decided to address the Constitutional Tribunal to examine the bill in order to check its compliance with the Polish Constitution. He blamed the regulation for infringing in particular the right to life and human dignity and exceeding the competences foreseen in the Constitution for the armed forces to exercise their powers within the state territory. The Tribunal in its sentence from Sept. 30, 2008 agreed with him and claimed a contradiction between the particu lar solutions and the dispositions of the Polish Constitution. Evaluating the legislation in force, it should be noticed that the state is not allowed to decide on whether its citizens on the ground or those on board of the plane shall survive. Allowing to shoot down a renegade type object means depriv ing those on board of the plane of their right to have their life protected, to secur ing which the state is obliged. It is particularly impermissible to allege in this context the potentially short period of time they have to live, to justify their sac rifice. It is also not allowed to treat the passengers and crew as part of the plane, therefore a part of the weapon used by the terrorists, as it constitutes the objec tification of a person, equal to depriving them of their innate and nonnegotiable dignity. It is also improper to create legislation fitting one particular, designated, existing or potential situation, including the occurrences of 11th September 2001. In conflict situations like the one we are dealing with here, it should be assumed, that the collisions of certain kinds of goods, that may not be framed within rigid legal norms, occur, furthermore, the legislator should not attempt to describe and decide on them in the content of a legal act. As even putting them within a legal framework will not change the illegality of every decision, finding the solution in such a situation should be left solely to a person in charge, judging in accordance with their own conscience and morality.